Anticorrosive properties in 1020 steel of an alkaloid-rich extract obtained from the jaborandi biomass (Pilocarpus microphyllus staff ex wardlew) of the pilocarpine industrial production chain - de Araújo, Francisco Marcelino Almeida (2024)
The annual costs related to corrosion and its prevention have been responsible for a significant part of the Gross Domestic Product in the Western world. In addition to economic costs and technological delays, corrosion can lead to structural failures having dramatic consequences for humans and the environment. In this context, the constant development of coating technology is needed. The search for natural products applied in anti-corrosive coatings has been of great industrial importance as they have a lower energy consumption in their production when compared to their synthetic counterparts. Plant extracts represent a rich source of natural chemical components that can be extracted by means of simple and low-cost procedures. In this research, an alkaloid-rich extract from the jaborandi leaf, with epiisopiloturine (EPI) as the major alkaloid, is investigated for its anti-corrosive activity. The investigation includes the coating formation on an AISI type 1020 steel substrate, which was submitted to accelerated corrosion tests and then to polarization analysis and impedance measurements in saline environment. The extract-covered plates proved to be corrosion-resistant in a saline environment. Thus, using computational chemistry, we propose an electrostatic interaction model that rationalizes the EPI adhesion on metal surfaces. Graphical abstract: (Figure presented.)